Transforming Finite Subordinate Sentences into Non- Finite and Verbless Sentences with Reference to Translation : A Contrastive Study (Journal of the College of Basic Education, 2024)
This study is a contrastive syntactic analysis for the purpose of showing the possibility of transforming finite subordinate sentences into non-finite and verbless sentences. Some English and Arabic adverbial finite sentences could be changed into non-finite or verbless sentences. This change may occur by ellipting some parts of the subordinate sentences or by converting the finite verb into a non-finite verb. The present study deals with the problem of transforming finite subordinate sentences into non-finite and verbless sentences as they appear within the context of the complex sentence. These sentences have different sorts of syntactic structures which could pose problems to translators. This study aims at demonstrating (1) Whether all types of English subordinate adverbial sentences, which have a finite verb, can be transformed into non-finite or verbless sentences and (2) Whether Arabic has surface structures which correspond to the English non-finite or verbless sentences. This study limits itself to the subordinate adverbial sentences as they appear within the context of the complex sentence. Other types of subordinate sentences, nominal or adjectival, are beyond the scope of this study. It is hoped that this study is of some theoretical and practical value to those concerned with syntactic structures and translation. The methodology adopted in dealing with the subject under investigation is Transformational- Generative Grammar.